Breast cancer in premenopausal women in rural Pakistan: A missing conversation - Shaikh, Fizza (Journal of the Pakistan Medical Association, 2026)
To The Editor, Breast cancer remains one of the most prevalent malignancies affecting women worldwide. The incidence of developing breast cancer has risen in Pakistan, with a lifetime risk of 1 in 9 women being diagnosed with the disease [1]. Traditionally breast cancer has been considered to primarily affect postmenopausal women, but in recent years, it has been increasingly diagnosed in premenopausal women. Early menarche, late menopause, use of OCPs, genetic mutations, radiation exposure, and obesity are well-known risk factors for the breast cancer in premenopausal women [2]. Despite the increasing amount body of evidence, awareness initiatives and screening methods in Pakistan largely target postmenopausal women. Young women, particularly those living in rural areas, are frequently left out of discussions related to prevention, diagnosis, and treatment. Studies show that women in Pakistan often seek health care only when cancer has reached its advanced stages due to a variety of socio-economic and cultural factors, including young age, job status, lack of awareness, anxiety regarding surgical procedures, and faith in alternative therapies and spiritual healing [3]. Yet, current public health strategies and awareness campaigns rarely address this vulnerable subgroup. It is therefore crucial to include this demographic in the national breast cancer conversation. The rising incidence of breast cancer among young women in rural setting highlights a silent crisis that needs an urgent attention. National health policies must ensure that this demographic subgroup is no longer overlooked in access to prevention, screening, and treatment facilities. A nationwide screening initiative, supported by multiple stakeholders, is crucial to reduce stigma and encourage screenings, particularly among younger and rural women [4]. Community-level awareness campaigns should be conducted to overcome existing barriers and to promote breast self-examination, screening, and treatment programmes.